The role of organizational and ethical factors in developing evidence-based strategic decision making in hospitals of Tehran University of Medical Sciences in Iran - Sohrabi, Samaneh; Mahfozpoor, Saad; Vahdat, Shaqayeq; Mahmodi, Mahmod; Rabiyi, Mahnaz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The present study aims to investigate the role of organizational and ethical factors in developing evidence-based strategic decision making in hospitals. The present study was a cross-sectional and qualitative study. The statistical population of the study included all knowledgeable experts in the field of hospital management in Tehran as well as managers of selected hospitals of Tehran University of Medical Sciences. The research tools included semi-structured interviews and a researcher-made questionnaire. Structural equation method was used to analyze the data of the present study using SPSS and PLS software. The results of this study showed that environmental factors including indoor and outdoor environment as well as organizational factors including educational factors, job factors, factors related to organization considerations, factors related to organization strategies, factors related to decision making, factors related to characteristics The decision process and factors are related to the nature of the decision. The results of the present model showed that environmental and organizational factors influence the development of evidence-based strategic decision making in hospitals.